Noise‐based logic locking scheme against signal probability skew analysis - Ahmad Rezaei; Ali Mahani (IET Computers & Digital Techniques)
Abstract Due to integrated circuit (IC) production chain globalisation, several new threats such as hardware trojans, counterfeiting and overproduction are threatening the IC industry. So logic locking is deployed to hinder these security threats. In this technique, an IC is locked, and its functionality is retrieved when the right key is loaded onto it. We propose ‘noise‐based’ logic locking, consisting of two separate compliment blocks, which function in three states. By flipping a signal once in the circuit, these modules add corruption to the circuit, whereas either flipping the same signal twice or not flipping leads to the correct functionality. Thus, a low probability skew with a low corruption in the output is obtained by utilisation of these flipping states. We have improved SAT attack resiliency based on time by 17% for a locking block with 14 primary inputs in comparison with the well‐known anti‐SAT. The area overhead is less in comparison with other schemes, in which extra dummy parts or obfuscation elements are added to their circuit. Also, more crucially, our locking blocks are immune to SPS attack solely. After executing various attacks, retrieved circuits indicate improved overall resiliency against automatic test pattern generation based and approximate guided removal attacks as well.